GPS analysis of a team competing in a national under 18 field hockey tournament - van der Merwe, F. H.; Haggie, M. B. P. (Journal of Australian Strength and Conditioning, 2019)
The running demands in regional male under 18 field hockey is position specific, therefore, training schedules, substitutions and intra-match recovery should be tailored by position, taking into account the needs of the individual players.